Negotiating Meaning and Position in Israel’s International Court of Justice Opening Statement: Discourse Tagging of Appraisal Categories - Abuelwafa, Marwa Adel (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2025)
The Appraisal Theory provides the means to recognize and categorize subjective opinions and emotions expressed in texts, whether positive or negative and explain how they manifest in language. Deeply rooted in Systemic Functional Grammar, the Appraisal Theory investigates the means of establishing, amplifying, targeting and sourcing of evaluation and attitude. Appraisal involves the negotiation of meaning and stance, which helps us understand the levels of emotional and ideological solidarity created by writers or speakers. In their texts, speakers/ writers adopt certain stances not only towards the information they present but also in solidarity with the audiences with whom they communicate, thus, serving their ideological purposes. This study aims to investigate the interpersonal dimension of discourse in the full text of Israel’s opening address against the South African genocide case at the International Court of Justice to clarify the position of the Israeli Foreign Ministry Legal Advisor Tal Becker. The study creates a tag set of the Appraisal categories, proposed by Martin and White (in The language of evaluation: Appraisal in english. Palgrave Macmillan, New York, 2005), in the Appraisal Model. The tag set created will be used to annotate the full text of Israel’s opening address, which serves as the data for the current study, and to investigate the language employed by the Israeli Legal Advisor concerning the current events in Gaza. Appraisal helps classify subjective opinions as a means to unfold many hidden secrets in texts.